Constructing spin crossover-fluorescence bifunctional iron(ii) complexes based on tetraphenyl ethylene-decorated AIEgens. Issue 16 (24th March 2023) - Yi, Cheng; Zhang, Shi-Hui; Zhao, Liang; Yao, Nian-Tao; Zhao, Guo-Hui; Meng, Yin-Shan; Liu, Tao
Abstract : Three new AIEgen-decorated mononuclear Fe II complexes were synthesized and characterized. Magnetic susceptibility and luminescence studies reveal these three complexes show SCO and AIE properties. Reasons for the absent synergy between SCO and luminescence were discussed. Abstract : Investigating spin crossover (SCO)-fluorescence bifunctional materials and establishing their structure–function relationships are attractive topics in chemistry and materials science. However, it remains challenging to preserve the fluorescence and SCO properties simultaneously in aggregated solid states. Herein, we design an ( E )-2, 6-bis(1 H -pyrazol-1-yl)-4-(4-(1, 2, 2-triphenylvinyl)styryl)pyridine (tpe-bpp) ligand, which contains coordinated SCO and fluorescence units of an aggregation-induced emission luminogen (AIEgen). The coordination of the tpe-bpp ligand with different Fe II salts generated three mononuclear complexes: [Fe(tpe-bpp)2 ](ClO4 )2 ·5.75CH2 Cl2 (1 ), [Fe(tpe-bpp)2 ](ClO4 )2 ·CH2 Cl2 ·3CH3 OH (2 ) and [Fe(tpe-bpp)2 ](BF4 )2 ·CH2 Cl2 ·3CH3 OH (3 ). Single-crystal X-ray diffraction studies showed that they shared a similar [Fe(tpe-bpp)2 ] 2+ complex cation. Their counterions and co-crystallized solvents were different. Magnetic measurements revealed that 1, 2, and 3 exhibited a complete SCO behavior with the transition temperatures T 1/2 of 375, 260, and 248 K, respectively. Fluorescence measurements confirmed the existence of the AIE property for both the tpe-bpp ligand and Fe(ii ) complexes. A monotonic decrease of the photoluminescence (PL) intensity upon increasing the temperature was behavior observed for all three complexes.